Fungsi Pengawasan Parlemen dalam Perspektif Gender - Aziz SR, Abdul (Journal of Politics and Policy, 2018)
As a branch of power in a democratic system, parliament has a function of control over the executive. This function is carried out to ensure that what is ordered by the Act is carried out properly by the executive, as well as to prevent at least minimizing deviations of power. In a gender perspective, the supervision carried out by parliament must accommodate and consider all interests for justice for all citizens. The interests of all citizens without discrimination against both men and women. Legislative activities and budget allocations carried out by the parliament together with the government must form a unity with a supervisory function to ensure the decision-making process along with political decisions that are gender responsive.